Independent Curriculum Innovation Model with a Semester Credit System Based on the Needs of Integrated Islamic Boarding School Students - Mohammad Zaini (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2024)
The Curriculum with the Semester Credit System (SKS) model adapts to students' learning speed to complete the competencies required in the Curriculum. This article describes the innovation of an independent curriculum with a formal semester credit system at the integrated Madrasah Aliyah level at the Miftahul Midad Lumajang Islamic boarding school. This research uses qualitative and descriptive methods through a case study approach. Research data analysis from interviews, observations, and documentation with reduction, display, and verification stages. Curriculum innovation model to improve the quality of Education at the Miftahul Midad Islamic Boarding School with five essential stages, namely: a) analysis of student needs, b) analysis of learning outcomes and essential competencies, c) preparation of the structure of curriculum material and, d) competency training for teaching staff, e) development of teacher competency.